MicroRNAs: exploring their role in farm animal disease and mycotoxin challenges - Kappari, Laharika; Dasireddy, Joseph Rishitha; Applegate, Todd J.; Selvaraj, Ramesh K.; Shanmugasundaram, Revathi (Frontiers in Veterinary Science, 2024)
MicroRNAs (miRNAs) serve as key regulators in gene expression and play a crucial role in immune responses, holding a significant promise for diagnosing and managing diseases in farm animals. This review article summarizes current research on the role of miRNAs in various farm animal diseases and mycotoxicosis, highlighting their potential as biomarkers and using them for mitigation strategies. Through an extensive literature review, we focused on the impact of miRNAs in the pathogenesis of several farm animal diseases, including viral and bacterial infections and mycotoxicosis. They regulate gene expression by inducing mRNA deadenylation, decay, or translational inhibition, significantly impacting cellular processes and protein synthesis. The research revealed specific miRNAs associated with the diseases; for instance, gga-miR-M4 is crucial in Marek's disease, and gga-miR-375 tumor-suppressing function in Avian Leukosis. In swine diseases such as Porcine Respiratory and Reproductive Syndrome (PRRS) and Swine influenza, miRNAs like miR-155 and miR-21-3p emerged as key regulatory factors. Additionally, our review highlighted the interaction between miRNAs and mycotoxins, suggesting miRNAs use as a biomarker for toxin exposure. For example, alterations in miRNA expression, such as the dysregulation observed in response to Aflatoxin B1 (AFB1) in chickens, may indicate potential mechanisms for toxin-induced changes in lipid metabolism leading to liver damage. Our findings highlight miRNAs potential in early disease detection and intervention in farm animal disease management, potentially reducing significant economic losses in agriculture. With only a fraction of miRNAs functionally characterized in farm animals, this review underlines more focused research on specific miRNAs altered in distinct diseases, using advanced technologies like CRISPR-Cas9 screening, single-cell sequencing, and integrated multi-omics approaches. Identifying specific miRNA targets offers a novel pathway for early disease detection and the development of mitigation strategies against mycotoxin exposure in farm animals.